Critical Care - Vincent, Jean-Louis
Critical Care is a high-quality, peer-reviewed, international clinical medical journal. Critical Care aims to improve the care of critically ill patients by acquiring, discussing, distributing, and promoting evidence-based information relevant to intensivists. Critical Care aims to provide a comprehensive overview of the intensive care field.